Psychological indicators for healthy aging: validation of the German short version of Ryff’s scales of psychological well-being (SPWB) - Ana N. Tibubos; Anna C. Reinwarth; Iris Reiner; Antonia M. Werner; Philipp S. Wild; Thomas Münzel; Jochem König; Karl J. Lackner; Norbert Pfeiffer; Manfred. E. Beutel (Journal of Patient-Reported Outcomes)
Abstract Background The important roles of well-being as realization of one’s true potential for healthy aging have been highlighted by literature of the recent decades. The Scales of Psychological Well-being (SPWB) are an internationally recognized measurement tool for psychological well-being. Yet, sound validation of the German SPWB 18-item version has been lacking to date. Therefore, the present study aims to (1) test the psychometric properties of the German SPWB 18-item version in terms of factorial validity and (2) determine construct validity by investigating its correlations with psychosocial variables, mental and physical health. (3) Sociodemographic characteristics of the SPWB in a middle to old age German population was explored. Methodology Data of N = 3,374 participants 45–85 years old of the 10-year follow-up (2017–2022) of the Gutenberg Health Study (GHS) were analyzed. Descriptive analyses and inference statistical analyses were performed to assess construct validity. In order to determine the psychometric properties, item characteristics and reliability coefficients were analyzed. Confirmatory factor analyses tested the proposed theoretical factorial structure. Results Construct validity of the SPWB was established with respect to sociodemographic, psychosocial (social support and resilient coping), and health variables (sleeping problems, depression and anxiety symptoms, stress, loneliness, and somatic diseases). Analysis of the psychometric properties of the German SPWB 18-item version rendered support for the theoretically proposed multidimensional structure of psychological well-being in our sample rather than a one factorial structure. Bi-factor models that take the method effects of positively and negatively formulated items into account are highly recommended. Conclusions The German SPWB 18-item version shows comparable psychometric properties to previous large-scale studies from other countries. The SPWB provides psychological indicators for healthy aging.